Assessment of pegylated arginine deiminase and modified FOLFOX6 in patients with advanced hepatocellular carcinoma: Results of an international, single‐arm, phase 2 study. Issue 24 (20th August 2021) - Harding, James J.; Yang, Tsai‐Sheng; Chen, Yen‐Yang; Feng, Yin‐Hsun; Yen, Chia‐Jui; Ho, Ching‐Liang; Huang, Wen‐Tsung; El Dika, Imane; Akce, Mehmet; Tan, Benjamin; Cohen, Stacey A.; Meyer, Timothy; et al.
Abstract : Background: Arginine starvation depletes the micronutrients required for DNA synthesis and interferes with both thymidylate synthetase activity and DNA repair pathways in preclinical models of hepatocellular carcinoma (HCC). Pegylated arginine deiminase (ADI‐PEG 20), an arginine degrader, potentiates the cytotoxic activity of platinum and pyrimidine antimetabolites in HCC cellular and murine models. Methods: This was a global, multicenter, open‐label, single‐arm, phase 2 trial of ADI‐PEG 20 and modified 5‐fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) in patients who had HCC with Child‐Pugh A cirrhosis and disease progression on ≥2 prior lines of treatment. The primary objective was the objective response rate assessed according to Response Evaluation Criteria in Solid Tumors, version 1.1. Secondary objectives were to estimate progression‐free survival, overall survival, safety, and tolerability. Eligible patients were treated with mFOLFOX6 intravenously biweekly at standard doses and ADI‐PEG‐20 intramuscularly weekly at 36 mg/m 2 . Results: In total, 140 patients with advanced HCC were enrolled. The median patient age was 62 years (range, 30‐85 years), 83% of patients were male, 76% were of Asian race, 56% had hepatitis B viremia, 10% had hepatitis C viremia, 100% had received ≥2 prior lines of systemic therapy, and 39% had received ≥3 prior lines of systemic therapy. The objective response rate was 9.3% (95% confidence interval [CI], 5.0%‐15.4%), with a median response duration of 10.2 months (95% CI, 5.8 months to not reached). The median progression‐free survival was 3.8 months (95% CI, 1.8‐6.3 months), and the median overall survival was 14.5 months (95% CI, 13.6‐20.9 months). The most common grade ≥3 treatment‐related events were neutropenia (32.9%), white blood cell count decrease (20%), platelet count decrease (19.3%), and anemia (9.3%). Conclusions: Concurrent mFOLFOX6 plus ADI‐PEG 20 exhibited limited antitumor activity in patients with treatment‐refractory HCC. The study was terminated early, and no further evaluation of the combination will be pursued. Lay Summary: Arginine is an important nutrient for hepatocellular carcinoma (HCC). The depletion of arginine with pegylated arginine deiminase (ADI‐PEG 20), an arginine degrader, appeared to make chemotherapy (FOLFOX) work better in animal models of HCC and in patients with HCC on an early phase clinical trial. To formally test this hypothesis in the clinical setting, a large, global, phase 2 clinical trial was conducted of ADI‐PEG 20 and FOLFOX in the treatment of patients with refractory HCC. The study showed limited activity of ADI‐PEG 20 and FOLFOX in advanced HCC and was stopped early. Abstract : Despite high‐level preclinical and early phase clinical data suggesting a potentiating effect of arginine depletion on 5‐fluorouracil, leucovorin, and oxaliplatin (FOLFOX) anticancer activity in hepatocellular carcinoma, a global, single‐arm, phase 2 study of pegylated arginine deiminase (ADI‐PEG 20) plus FOLFOX in patients with hepatocellular carcinoma who progressed on 2 lines of systemic therapy failed to meet its primary end point. There is no role for the combination of AGI‐PEG 20 and FOLFOX in advanced hepatocellular carcinoma.